Humanizing Education in Virtual Learning Environment: Experience of Students in Al-Madinah International University - Hamed, Popoola Kareem; Mohammed, Ayman Aied; Mohamed, El Sayed Salem; Fath El-Bab, Mohamed Salah El-Din Ahmed (Ijaz Arabi Journal of Arabic Learning, 2024)
Online learning needs to humanize the experience, especially in this day and age when technology is upending our lives and curriculum delivery methods are evolving quickly with new tools and applications. It is crucial, therefore, to humanize both our instruction and our students' learning at disruptive moments. This study aimed to investigate how Al-Madinah International University (MEDIU) undergraduate students experienced humanizing learning in a virtual learning environment. The researchers use a sequential mixed-method methodology to collect information to analyze the humanization of education in virtual learning environments. (320) undergraduate students from Al-Madinah International University participated in the quantitative portion of the study by answering both open-ended and closed-ended questionnaires. The qualitative data was analyzed using a thematic method, and the results were used to support the quantitative findings by creating themes using ATLASTI. The quantitative data was analyzed using descriptive statistics. According to the study's findings, 87% of respondents said that humanizing education in a virtual learning environment was successfully applied. At the same time, the remaining respondents were unsure. According to the qualitative data, most ODL instructors must attend training on using humanizing education in virtual learning environments. During the module compilation process, the participants suggested that ODL programs incorporate the cultural information students have learned at home and in their communities. Most respondents have an Arabic language background, so the curriculum needs to consider their culture. Students from Arabic and Islamic backgrounds, in particular, should have their culture at the center of lectures in the virtual learning environment, according to the institution.